Anterior Cranial Fossa Dural Arteriovenous Fistula Presenting as Recurrent Multifocal Lobar Intracerebral Hemorrhages: A Case Report. (April 2019) - Johnson, Stephen Abraham; Cox, Benjamin; Ho, Mai Lan; Murphy, Meghan; Scharf, Eugene
We report a unique case and presentation of a 77-year-old man with atrial fibrillation who presented with complex imaging features, including bifrontal cerebral hematomas that progressed to multifocal macro- and microhemorrhages, vasogenic edema, and cortical/meningeal enhancement. Cerebrospinal fluid analysis was only remarkable for a protein elevation of 65 mg/dL. Leptomeningeal vessel biopsy failed to demonstrate evidence of amyloid angiopathy but did show concentric obstructive intimal fibroplasia, suggestive of chronic venous congestion. Conventional cerebral angiography showed a Cognard type IV dural arteriovenous fistulae fed by bilateral ethmoidal arteries draining directly into ectatic cortical veins. A chronic occlusion of the anterior third of the superior sagittal sinus was also noted. The fistula was successfully surgically obliterated via an uncomplicated left frontal craniotomy approach. After rehabilitation therapy, he was discharged home with a modified Rankin Scale score of 3. Because effective treatment exists, this case underscores the importance of identifying this rare etiology of intracerebral hemorrhage and pursuing adequate workup.